Emergency Department Management of Recent-Onset Atrial Fibrillation. (July 2020) - Weant, Kyle A.; Matuskowitz, Andrew J.; Gregory, Haili; Caporossi, Jeffrey; Hall, Gregory A.
Abstract : Atrial fibrillation (AF) is the most common tachyarrhythmia managed in the emergency department (ED). Visits to the ED for a presentation of AF have been increasing in recent years, with an admission rate that exceeds 60% in the United States and contributes substantially to health care costs. Recent-onset AF—defined as symptom onset less than 48 hr—is a common ED presentation for which rate control or acute electrical or pharmacological cardioversion may be appropriate treatment modalities depending on patient-specific circumstances. The focus of this review is to discuss the current recommendations regarding the management of recent-onset nonvalvular AF in the ED, discuss medication administration considerations, and identify implementation strategies in the ED to optimize throughput and reduce hospital admissions.